Utilization of the 915 MHz LoRa Communication Module as a Navigational Tool in Rural Areas - Hadikusuma, Ridwan Satrio; Azhar, Nur Wahid (Majalah Ilmiah Teknologi Elektro; Vol 22 No 1 (2023): (Januari - Juni) Majalah Ilmiah Teknologi Elektro, 2023)
The high interest of mountain climbers in Indonesia also increases the risk of accidents that can occur in climbing. To reduce this risk, we need a tool system that can assist local officers in monitoring the location and condition of climbers. However, due to the many signal limitations and internet connections in mountainous terrain or rural areas, there is a need for other alternative media that can be used to monitor climbers' location and conditions. The LoRa (Long Range) communication module can solve the mountain's limited signal and internet connection. Navigation uses the LoRa SX1276 module based on Radio Frequency (RF) as the transmission medium in the 915 MHz frequency range. The data transmission uses the repeater principle as a bridging medium between devices which can then be displayed via the Android application via Cloud Firestore or Bluetooth media. From the results of the tests that have been carried out, it can be concluded that the system works well in transmitting data via Radio Frequency (RF) with an average RSS reduction of -5.1 dBm every 45 m at a radius of 450 m, Cloud Firestore with an average delay of 0.3855 seconds and Bluetooth with reduced RSSI of -5.5 dBm every 5 m with a maximum radius of 50m. Keyword—Radio Frequency(RF), Wireless, Aplication Android, Cloud Firestore, LoRa.